The aspects of potential hybrid warfare in the Republic of Serbia - Rašković Talović, Violeta (Napredak, 2022)
The research presents an analysis of the phenomenon of hybrid warfare as a strategy in which conventional means of warfare are combined with unconventional methods and aspects of a possible hybrid war in Serbia. In the past, the domination of one country, i.e., the surrender of the opposing one, was achieved by war in the traditional sense – armed struggle. The essence of armed struggle was either the achievement of respectable military superiority or complete destruction of the enemy’s armed forces. If the attacked country could not organize military opposition, it would most often be forced to fulfil the required concessions of the victorious country or to obey it completely. However, even then, the end of the armed struggle did not guarantee that liberation aspirations of the vanquished would be suppressed, i.e., complete capitulation did not necessarily lead to permanent demise of a country and assimilation of its population into a victorious country.
Keywords: hybrid warfare; power; domination; manipulation; international relations; Serbia